A Case of Immunotherapy-Induced Colitis Complicated by Perforation and Treated with Infliximab Postoperatively - Lukas Delasos; Aakash Desai; Nerea Lopetegui Lia; Nikhila Kethireddy; Carolyn Ray (Case Reports in Oncological Medicine)
The advent of checkpoint inhibitor therapy in medical oncology has led to an increase in hospitalizations for immune-related adverse effects. Severe colitis has been reported in approximately 5% of patients treated with cytotoxic T-lymphocyte-associated antigen-4 (CTLA-4) inhibitors, such as ipilimumab. Standard management for those with severe colitis includes administration of systemic corticosteroids with the reservation of antitumor necrosis factor (anti-TNF) therapy, such as infliximab, if there has been no improvement. Rarely, immunotherapy-induced colitis can become life-threatening and result in bowel perforation requiring surgical intervention. Yet, there are no specific recommendations for medical management following colectomy in these situations. In cases of severe colitis from Crohn’s disease, postoperative treatment with infliximab has been found to be safe when administered shortly after intestinal resection. However, there remains limited data to support administration of infliximab following bowel perforation due to immunotherapy-induced colitis. Our case illustrates management of a severe adverse reaction to checkpoint inhibitor therapy and the need to further evaluate the role of infliximab postoperatively in patients who develop colitis complicated by bowel perforation.